Preterm Births and Educational Disadvantage: Heterogeneous Effects Across Families and Schools - Anna Baranowska-Rataj; Kieron Barclay; Joan Costa-i-Font; Mikko Myrskylä; Berkay Özcan (Center for Economic Studies and ifo Institute (CESifo), 2019)
Using Swedish population register data on cohorts born 1982-1994 (N=1,087,750), we examine the effects of preterm births on school grades using sibling fixed effect models which compare individuals with their non-preterm siblings. We test for heterogeneous effects by degree of prematurity, as well as whether family socioeconomic resources and school characteristics can compensate for any negative effects of premature births. Our results show that preterm births can have negative effects on school grades, but these negative effects are largely confined to children born extremely preterm (<28 weeks of gestation, i.e. born at least 10 weeks earlier). Children born moderately preterm (i.e. born up to 5 weeks early) suffer no ill effects. We do not find any evidence for the moderating effect of parental socioeconomic resources. Our results indicate that school environment is very important for the outcomes of preterm born children, such that those born extremely preterm that are in the top decile of schools have as good grades as those born full-term that are in an average school. However, good schools appear to lift scores for all groups, and as a result that gap between extremely preterm and full-term children remains also in the best schools. This highlights the role of schools as institutions that may either reduce or reinforce the early life course disadvantage.
Keywords: I10; I20; J13; 330; premature births; human capital; early life investments; education investments; Sweden